For the common good and their own well-being : social estates in Imperial Russia - Smith, Alison Karen (Oxford University Press, 2015)
"This book shows how the imperial Russian system of social estates (sosloviia), which derived from the government's need to categorize and rank its subjects, held power over individual identities and life choices in Russia throughout the eighteenth and nineteenth centuries. Though in part modeled on the orders of old regime Europe, also called estates, the Russian system had its own peculiarities, two of which include the imprecision in the (oft changing) laws of its rules and procedures, allowing for endless interpretations and realignments, and its stamina, not being swept away until the Bolshevik Revolution of 1917. For the imperial state, estates were a means of making the population productive; for individuals, they were a source not only of individual identity, but of community, in ways at times demanding and at times supportive"--Provided by publisher